OBJECTIVES, TASKS AND PRINCIPLES OF EFFICIENT MANAGEMENT OF ENTERPRISES (American Journal of Business Management, Economics and Banking, 2026)
Recently, issues related to profit management have become increasingly relevant both theoretically and practically. Profit characterizes the financial results of the organization for a certain period of time and is one of the main indicators that external contractors and owners make decisions about the company. At the same time, it should be remembered that the profit performs the function of an accounting indicator, which is calculated in accordance with the approved accounting standards. One of the fundamental printouts of the account-the application of the method of calculation – leads the managers of the company to the fact that it is necessary to make decisions on determining the main elements of profit (income and expenses), as well as the time of their evaluation.